If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x + -10) = ln(19) Reorder the terms: ln(-10 + 5x) = ln(19) (-10 * ln + 5x * ln) = ln(19) (-10ln + 5lnx) = ln(19) Reorder the terms for easier multiplication: -10ln + 5lnx = 19ln Solving -10ln + 5lnx = 19ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-19ln' to each side of the equation. -10ln + -19ln + 5lnx = 19ln + -19ln Combine like terms: -10ln + -19ln = -29ln -29ln + 5lnx = 19ln + -19ln Combine like terms: 19ln + -19ln = 0 -29ln + 5lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-29 + 5x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-29 + 5x)' equal to zero and attempt to solve: Simplifying -29 + 5x = 0 Solving -29 + 5x = 0 Move all terms containing l to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 5x = 0 + 29 Combine like terms: -29 + 29 = 0 0 + 5x = 0 + 29 5x = 0 + 29 Combine like terms: 0 + 29 = 29 5x = 29 Add '-5x' to each side of the equation. 5x + -5x = 29 + -5x Combine like terms: 5x + -5x = 0 0 = 29 + -5x Simplifying 0 = 29 + -5x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| ln(5x+10)=ln(19) | | 0.7x-0.3=0.6x+5 | | -40+9x=-11x+4(5x+12) | | 9=1a/7a | | -4x+4y=16 | | 232+6(log)x=190 | | x+y+2y=45 | | -27.0=-4.5c | | -6x+y=24 | | -2x^2+5=3x-3 | | 51=x+4x+(x+3) | | -4(4)+4y=16 | | 6+z*10=-2 | | 2x/7x=3 | | x(15x+4)=32 | | 6x-6=4x+10 | | 2x/8x=3 | | f(x)=x^3+6x^2+3x-10 | | -6(4)+y=24 | | -12(2n+11)=3(5n-5) | | 6x-1=27-x | | 5+log^4(-4x)=7 | | 3x+2(x-7)=(9x-1)-(x-8) | | -6x+(-6x+24)=24 | | 10x+8=158 | | 300=x+(x+20) | | n+3*8=-4 | | .5(4x-10)=15 | | (h-6)=2(5-2h) | | 2/7(x)= | | x+7=x-31 | | 29x-17y=-7 |